2015
DOI: 10.1371/journal.pone.0141758
|View full text |Cite
|
Sign up to set email alerts
|

Enzymatic Characterization of Recombinant Food Vacuole Plasmepsin 4 from the Rodent Malaria Parasite Plasmodium berghei

Abstract: The rodent malaria parasite Plasmodium berghei is a practical model organism for experimental studies of human malaria. Plasmepsins are a class of aspartic proteinase isoforms that exert multiple pathological effects in malaria parasites. Plasmepsins residing in the food vacuole (FV) of the parasite hydrolyze hemoglobin in red blood cells. In this study, we cloned PbPM4, the FV plasmepsin gene of P. berghei that encoded an N-terminally truncated pro-segment and the mature enzyme from genomic DNA. We over-expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…Recombinant PM4s from the other three human malaria parasites and the rodent malarial parasite P. berghei were similarly produced and activated [54,126,133]. The subsite specificity at S3 -S3' of the five PM4 orthologs (i.e., PfPM4, PoPM4, PvPM4, PmPM4 and PbPM4) was investigated using combinatorial peptide libraries [125,133]. All five PM4s unanimously prefer accommodating phenylalanine or tyrosine at S1 and S1', except that PbPM4 accommodates norleucine best at S1'.…”
Section: Plasmepsin 4 Orthologsmentioning
confidence: 99%
“…Recombinant PM4s from the other three human malaria parasites and the rodent malarial parasite P. berghei were similarly produced and activated [54,126,133]. The subsite specificity at S3 -S3' of the five PM4 orthologs (i.e., PfPM4, PoPM4, PvPM4, PmPM4 and PbPM4) was investigated using combinatorial peptide libraries [125,133]. All five PM4s unanimously prefer accommodating phenylalanine or tyrosine at S1 and S1', except that PbPM4 accommodates norleucine best at S1'.…”
Section: Plasmepsin 4 Orthologsmentioning
confidence: 99%
“…It has also been shown that the prosegment does not suppress the activity of the mature part, which then can cleave a substrate peptide [37]. It was observed that pro-tPM from P. berghei could bind a substrate in the active site cleft even in the presence of the prosegment [38]. The pro-tPMV zymogen is catalytically active [39,40] and no release of prosegment is observed under acidic conditions, both during auto-activation and in vivo [39,41].…”
Section: Discussionmentioning
confidence: 99%
“…malariae as well as in the rodent malaria parasite P . berghei , Plasmepsin 4 (PM4) is the only aspartic protease localised within the digestive vacuole [ 22 , 23 ]. The PM5, PM9 and PM10 are the other aspartyl proteases expressed within asexual blood stage of the malaria parasite but not localised within the digestive vacuole [ 24 ].…”
Section: Introductionmentioning
confidence: 99%